A rare cause of dyspnea on exertion with a cardiopulmonary exercise stress test - Elizabeth H. Lees; Hernan Cardozo Torres; Eric S. Edell; Gustavo Cortes Puentes; Thomas A. Foley; Janani S. Reisenauer; Thomas G. Allison (Respiratory Medicine Case Reports)
Informative abstract: Background: It is rare for an adult patient to be living decades after a pneumonectomy procedure. This case features complications that can arise. We utilize cardiopulmonary exercise stress testing (CPET) to highlight long-term physiologic changes that can present in a post-pneumonectomy patient. Case presentation: A 53-year-old woman presented for cardiopulmonary exercise stress testing (CPET) to assess worsening dyspnea on exertion with associated chest pressure. She had a history of traumatic right-sided pneumonectomy at age 27 years complicated by post-pneumonectomy syndrome. Her CPET was suboptimal with marked deficiencies that were most consistent with a primary ventilation limitation causing her reduced exercise capacity. Discussion/conclusion: A thorough literature search did not return any similar cases using CPET to evaluate a post-pneumonectomy patient. The abnormal anatomy results in a unique set of CPET values. Her ventilatory insufficiency is likely made worse by her post-pneumonectomy syndrome. Her treatment options are limited.